2005
DOI: 10.1136/bmj.38586.411273.e0
|View full text |Cite
|
Sign up to set email alerts
|

Being big or growing fast: systematic review of size and growth in infancy and later obesity

Abstract: Objectives To assess the association between infant size or growth and subsequent obesity and to determine if any association has been stable over time. Design Systematic review. Data sources Medline, Embase, bibliographies of included studies, contact with first authors of included studies and other experts. Inclusion criteria Studies that assessed the relation between infant size or growth during the first two years of life and subsequent obesity. Main outcome measure Obesity at any age after infancy. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

41
837
4
31

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,027 publications
(913 citation statements)
references
References 33 publications
41
837
4
31
Order By: Relevance
“…Although no previous studies have explicitly investigated the effect of the location of the BMI peak on later levels of BMI, many studies have investigated the relationships between size and/or growth in infancy and later obesity [7][8][9][10] . The majority of studies have quantified infant size and (particularly) growth in terms of weight, which we have not modelled, but some have used BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no previous studies have explicitly investigated the effect of the location of the BMI peak on later levels of BMI, many studies have investigated the relationships between size and/or growth in infancy and later obesity [7][8][9][10] . The majority of studies have quantified infant size and (particularly) growth in terms of weight, which we have not modelled, but some have used BMI.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Baird et al 7 identified 18 studies concerning infant size, 11 of which found that infants who were heavier during infancy or were defined as obese were more likely to develop obesity in childhood, adolescence or adulthood. Several reviews, ranging in size from 10 to 21 studies, have focused on infant growth as an exposure [7][8][9] . The majority of studies in each review found more rapid growth in infancy to be associated with a greater risk of subsequent obesity.…”
Section: Introductionmentioning
confidence: 99%
“…2 These results are especially alarming as overweight children show a high risk of becoming obese adults. 3,4 Childhood is an important period of life for health interventions as health-related behaviors are just in formation, and it seems possible to intervene for preventing the development of obesity. 5 Thus, it is crucial to further understand the background mechanisms of childhood obesity to find even more effective measures to prevent it before it begins to produce more or less irreversible health damages.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, early nutritional practices have not been backed by rigorous experimental evidence of efficacy and safety, which is expected in other areas of public health; and have the potential to cause harm. For example, 'intuitive' attempts to promote growth in small, growth-retarded newborns could significantly increase later CVD and obesity (3)(4)(5)(8)(9)(10)(11)(12)(13)(14) . This lack of a sound evidence-base has prevented changes to nutritional and public health practice in infancy in order to prevent later NCD.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…For instance, faster weight gain in infancy (upward centile crossing for weight) is associated with a greater risk of later obesity in more than thirty studies (summarised in five systematic reviews, (8)(9)(10)(11)(12) including an individual-level meta-analysis in 47 661 participants from ten cohorts (11) ). This association is seen for the main components of the metabolic syndrome, in breast-fed and formula-fed populations, in high-and low-income countries representing many different ethnic groups (7)(8)(9)(10)(11)(12) , and is consistent for cohorts during the past 80 years (8) . The association is biologically plausible and experimentally reproducible in several animal models (7) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%